Brief historical notes on the Peruvian electricity sector and the Peruvian power transmission sector - Velásquez Chumpitaz, Jairo Jeyko (2020)
Currently, the use of electric energy is everywhere; however, this normalization has made many people unaware of its origins and the different stages through which this sector and, with special emphasis, the electric power transmission subsector, has gone through. Thus, in this new post-COVID panorama, numerous reforms and state plans on various economic and social areas are placed on the table for the «new normality», of which the electricity sector is viewed with a vital perspective in the present and in the future. Therefore, a historical review and knowledge of its origins is necessary for the configuration of this «new panorama», and in the future, in order to learn from the past so as not to make the same mistakes in the present and in the future. The electricity sector is the cornerstone and deserves more and better research in our country.